2017
DOI: 10.1152/ajpheart.00107.2017
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of two-pore K+ channels to cardiac ventricular action potential revealed using human iPSC-derived cardiomyocytes

Abstract: Two-pore K (K) channels have been described in modulating background conductance as leak channels in different physiological systems. In the heart, the expression of K channels is heterogeneous with equivocation regarding their functional role. Our objective was to determine the K expression profile and their physiological and pathophysiological contribution to cardiac electrophysiology. Induced pluripotent stem cells (iPSCs) generated from humans were differentiated into cardiomyocytes (iPSC-CMs). mRNA was is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…Additionally, Decher et al identified a mechanism in a patient whereby increased sodium permeability through a K 2p (TREK-1) predisposed the individual to right ventricular outflow tract ventricular tachycardia (34). Finally, recent work from our laboratory corroborates the notion that K 2p channels are more than simply background leak channels, acting as active participants in ventricular repolarization (35). Collectively, this evidence supports the idea that K 2p channels may modulate cardiomyocyte excitability and contribute to disease phenotypes as well as providing a therapeutic target.…”
Section: Introductionsupporting
confidence: 53%
“…Additionally, Decher et al identified a mechanism in a patient whereby increased sodium permeability through a K 2p (TREK-1) predisposed the individual to right ventricular outflow tract ventricular tachycardia (34). Finally, recent work from our laboratory corroborates the notion that K 2p channels are more than simply background leak channels, acting as active participants in ventricular repolarization (35). Collectively, this evidence supports the idea that K 2p channels may modulate cardiomyocyte excitability and contribute to disease phenotypes as well as providing a therapeutic target.…”
Section: Introductionsupporting
confidence: 53%
“…We showed that in the Kcnk3 deficient rat or with chronic pharmacological inhibition of KCNK3 with the compound A293 in healthy rats there was also increased heart rate compared to wild‐type or vehicle‐exposed rats, respectively (Lambert et al., 2018, 2019), confirming that KCNK3 function is essential for the control of heart rate. In human pluripotent stem cell‐derived cardiomyocytes, the knockdown of KCNK3 induced a significant prolongation of APD, confirming the contribution of KCNK3 in AP repolarization in human cardiomyocytes (Chai et al., 2017). In this way, KCNK3 appears to have an atrial‐specific expression in the human heart and generates electrical impulses.…”
Section: Introductionsupporting
confidence: 60%
“…Two-pore potassium channels ( K 2p ) usually generate an outward potassium current and are also known as potassium leak channels. When silencing the KCNK6 gene in the human heart, the action potential duration is prolongated ( Chai et al 2017 ). Another voltage-gated potassium channel gene KCNQ5 was decreasingly expressed in elongated EOD Campylomormyrus species.…”
Section: Discussionmentioning
confidence: 99%